Insights into the structure and electrochemical properties of Ti3C2T x MXene from solid-state NMR - Balasubramanian, Rajalakshmi; Puthiyaveetil, Priyanka Pandinhare; Kurungot, Sreekumar; Ajithkumar, T. G. (Journal of Physical Chemistry C, 2026)
Ever since their discovery in 2011, MXenes have gained popularity in energy storage devices. Their far-reaching properties arise mainly due to surface terminations and interlayer species like hydrated cations and water. The nature of these species remains a subject of study due to the complex surface functionalization during synthesis. X-ray diffraction studies have shown that certain intercalants such as hydrated cations increase the interlayer spacing leading to enhanced electrochemical performance. However, the structural and chemical modification of these intercalants during the charge-discharge cycles of asymmetric supercapacitors are yet to be investigated. Analysis of the complex chemistry of Ti3C2Tx requires a specialized tool that can provide insights into its nuanced structural changes and link them to its behavior. In this study, we demonstrate the versatility of solid-state NMR (SSNMR), for the characterization of surface terminations and intercalants in the Ti3C2Tx MXene prepared using sodium salts, and correlate its structure to its performance by ex situ SSNMR analysis. Our experiments demonstrate the progressive oxidation of surface Ti-OH and also the significance of the intercalated hydrated cation shells during electrochemical cycling. In addition to this, we have also employed Na-23 MAS SSNMR to demonstrate the conversion of sodium hexahydrate to sodium peroxides after 10 charge-discharge cycles.